Efeitos do exercício físico e do extrato de soja no perfil lipídico, no estresse oxidativo e na aterosclerose em camundongos deficientes do gene para receptor de LDR-/- - Tatiana Ramos Fonseca (2007)
Purpose: The present study had an objective to evaluate the effects of physical exercise and soy extract on lipid profile, oxidative stress and atherosclerosis in mice knockout for LDL receptor. Methods: The animals were divided into four groups: control diet (CT; n=8); control diet with physical exercise (EX; n=8); diet containing soy extract (ES; n=8) and diet containing soy extract with physical exercise (EX+ES; n=8). The duration of the experiment was for 6 weeks. The body weight and the relative heart weight were evaluated at the end of the experiment, also the total serum cholesterol, HDLc and atherogenic fractions, the lag time of conjugate diene production on serum and TBARS in kidneys and livers. Histomorphometrical analyses of aortic lesion on the aortic root and thoracic-abdominal aorta were performed. Results: We observed that only soy extract increased HDLc (CT: 21,01 + 2,05; EX: 22,92 + 3, 46; ES: 36,02 + 4,37; ES+EX: 32,77 + 6,52 mg/dL, p < 0,05) and reduced atherogenic fraction (CT: 650,77 + 86,10; EX: 668,03 + 55,07; ES: 551,29 + 63,63; ES+EX: 601,20 + 106,59 mg/dL, p < 0,05) on lipid profile. Regarding to serum lipid peroxidation resistance, physical exercise and soy extract prolonged the lag time stage when administrated together (CT: 3,40; EX: 8,40; ES: 9,40; EX+ES: 58,40 min, p < 0,05). Besides that, physical exercise and soy extract reduced TBARS levels in hepatic tissue (CT: 2, 28 + 0,33; EX: 1,04 + 0,21; ES: 1,36 + 0,35; EX+ES: 1,44 + 0,48 nmol de MDA/mg de proteína, p < 0,05). Although, were not noted effects of physical exercise and soy extract on atherosclerosis on thoracic-abdominal aorta, both promoted aortic lesion reduction on the aortic root (CT:598 x 103 + 146 x 103; EX: 319 x 103 + 91 x 103; ES: 301 x 103 + 73 x 103; EX + ES:188 x 103 + 36 x 103 m2, p < 0,05).Conclusion: The present study demonstrated that both, physical exercise and soy extract reduce atherosclerosis development on aortic root in LDLr -/- mice.